The Vital Spark : the British Coastal Trade, 1700-1930. - Armstrong, John (Research in Maritime History LUP., 2017)
This book collects seventeen previously published essays by John Armstrong concerning the British coastal trade. Armstrong is a leading maritime historian and the essays provided here offer a thorough exploration of the British coastal trade, his specialisation, during the period of industrialisation and technological development that would lead to modern shipping.